Role of Ethics in Procurement Process Effectiveness in the Water Sector in Kenya: (A Case Study of EWASCO, Embu County) - Jackson Ndolo; Eunice G. Njagi (International Journal of Supply Chain Management, 2014)
This paper is part of a study that sought to establish factors that affect effectiveness of the procurement process in water companies. The particular factors identified were documentation, electronic procurement, staff training, government policy and procurement ethics. The paper supports the perspective that ethical practices in the procurement process are a key pillar of its effectiveness. The paper proposes that an ethical based and effective procurement process can be built on the regulatory, corporate and functional legal framework for the benefit of all stakeholders in the water sector. The researchers adopted a descriptive research design. The analysis involved primary data obtained through questionnaires, interviews and secondary data which was obtained from relevant journals and books. The study was based on Embu Water and Sanitation Company, a leading water company whose core business is to provide clean drinking water in Embu County and its environs. It was evident from the findings that EWASCO procurement process was not effective as indicated by 88 percent of the responses. It was also found that the firm had no staff training on policy of the process with majority of the staff involved in procurement just relying on seminar trainings to run the procurement unit. The procurement department did not even have any ethical code to guide the staff involved in the process.The findings from the research confirmed that there is need to establish training programs as well as maintaining high organizational culture through strong codes of ethics. Overall there was the felt need to distribute and train personnel on the Public Procurement and Disposal Act policies and procedures. This study contributes to our knowledge on procurement process by presenting the key role of ethics on effective procurement process through personnel training on public procurement policies and procedures more so ethical regulations.